Phagocytosis of Anaplasma marginale infected and uninfected erythrocytes by bovine peripheral blood leukocytes - Meléndez, R.D. (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
The process of phagocytosis carried out by calf peripheral blood leukocytes (PBLs) on Anaplasma marginale infected or uninfected red blood cells (RBCs) in front of four different bovine sera was evaluated in vitro. Eight tests were run in a microplate containing PBLs, normal bovine erythrocytes (NBE) or A. marginale infected bovine erythrocytes (IBE), and either normal bovine serum (NBS), normal calf serum (NCS), vaccinated immune serum (VIS) or immune serum (IS). Erythrophagocytosis was detected in all tests that had IBE except in the test with NCS, and it was not detected in tests that had NBE, except in the test with NBS. The addition of IS and IBE to PBLs increased significantly (P< 0.01) the percentage of erythrophagocytosis when it was compared with the percentage detected in the tests that used NBS, VIS or IBE respectively. A 4% and 9% phagocytosis was detected in both tests performed with NBS. PBLs phagocytosed almost three times more NBE than IBE. In agreement with previous reports this study shows that IS, probably through specific immunoglobulins, mediates and enhances the process of erythrophagocytosis observed in vitro, which in vivo leads to severe anaemia; whereas the detection of phagocytosis in both tests with NBS would be explained either by a cross-reaction against A. marginale epitopes or by the presence of autoantibodies against cattle RBCs in the NBS or by other mediators like C3b. In conclusion, erythrophagocytosis, appears to be an antibody-dependent mechanism greatly responsable for the etiology of the severe anemia observed during the prepatent and patent periods of cattle anaplasmosis.